2017
DOI: 10.1177/0165025416687414
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary practices, metaparenting, and the quality of parent–child relationships in African-American, Mexican-American, and European-American mothers

Abstract: Coercive responses to children’s behavior are well recognized to be problematic for children’s adjustment. Less well understood is how parental social cognition is linked to discipline. In this study we sought to link metaparenting — parents’ thoughts about their parenting — to the use of coercive discipline. We predicted that mothers who engaged in more metaparenting, thus reflecting more deliberate parenting, would use corporal punishment less frequently and instead engage in non-coercive discipline. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…The mothers did not mention the child’s gender as a factor for different discipline choices. While Barajas-Gonzalez et al (2018) found male children to be spanked more often than female children, Holden et al (2017) found gender not to be a contributing factor to choice of discipline.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The mothers did not mention the child’s gender as a factor for different discipline choices. While Barajas-Gonzalez et al (2018) found male children to be spanked more often than female children, Holden et al (2017) found gender not to be a contributing factor to choice of discipline.…”
Section: Resultsmentioning
confidence: 90%
“…This misconception has been debated by scholars that state that Latino families with strong cultural values such as familismo are less likely to resort to harsher discipline strategies (Coohey, 2001;Lee & Altschul, 2015). Furthermore, some researchers have found that Latino families are less likely to spank their children compared to African American or Caucasian families (Holden et. al., 2017;Slade & Wissow, 2004).…”
Section: Latino Discipline Practicesmentioning
confidence: 99%
“…When parents were compared on the subscales of the Meta-parenting questionnaire, there was no significant difference between the mothers and fathers though it can be seen from Table 2 that mothers have scored slightly higher on the subscales assessing, anticipation, reflection, rumination, and total score whereas the fathers have scored slightly higher on the subscale problem solving of MPQ. [14]. It is important to note that scores of the Indian parent population are notably less as compared to the above-mentioned population which may be indicating that Indian parents are engaging in meta-parenting a lot less as compared to Western parents.…”
Section: Results and Discussion: -mentioning
confidence: 91%
“…A menudo los padres se muestran ambivalentes hacia el uso del castigo físico y es frecuente que manifiesten actitudes negativas hacia este pero continúan utilizándolo a pesar de no creer en su efectividad (Bunting, Webb and Healy, 2010). Otras variables más dinámicas como el estrés parental (Fráchette y Romano, 2015), cuestiones étnicas o culturales (Holden, Hawk, Smith, Singh y Ashraf, 2017; Khoury-Kassabri, Attar-Schwartz y Zur, 2014) son también importantes.…”
Section: Introductionunclassified